Interaction of phenolic acids and their derivatives with human serum albumin: Structure–affinity relationships and effects on antioxidant activity. (1st February 2018) - Zhang, Yunyue; Wu, Simin; Qin, Yinghui; Liu, Jiaxin; Liu, Jingwen; Wang, Qingyu; Ren, Fazheng; Zhang, Hao
Highlights: A comprehensive mathematical model improves the accuracy of results. The affinities with HSA are influenced by structure properties of phenolic acids. Hydrophobic force is involved in the binding between HSA and phenolic acids. Binding to HSA increases the antioxidant activity of phenolic acids. Abstract: In this study, 111 phenolic acids and their derivatives were chosen to investigate their structure–affinity relationships when binding to human serum albumin (HSA), and effects on their antioxidant activity. A comprehensive mathematical model was employed to calculate the binding constants, using a fluorescence quenching method, and this was corrected for the inner-filter effect to improve accuracy. We found that a hydroxy group at the 2-position of the benzene ring exerted a positive effect on the affinities, while a 4-hydroxy substituent had a negative influence. Both methylation of the hydroxy groups and replacing the hydroxy groups with methyl groups at the 3- and 4-positions of the benzene ring enhanced the binding affinities. Hydrophobic force and hydrogen bonding were binding forces for the phenolic acids, and their methyl esters, respectively. The antioxidant activity of the HSA–phenolic acid interaction compounds was higher than that of the phenolic acids alone.